Apple stem grooving virus (ASGV) and apple stem pitting virus (ASPV) : detection and isolate characterization in South African pome fruit - Gagiano, Magdalena Christiena (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.